1992
DOI: 10.7164/antibiotics.45.984
|View full text |Cite
|
Sign up to set email alerts
|

Neomycin biosynthesis: The incorporation of D-6-deoxy-glucose derivatives and variously labelled glucose into the 2-deoxystreptamine ring. Postulated involvement of 2-deoxyinosose synthase in the biosynthesis.

Abstract: D-[6-3H3]6-Deoxy-5-ketoglucose(10) and D-[5,6-3H2]6-deoxyglucose (ll) were incorporated into neomycins B and C using a growing culture of Streptomyces fradiae. D-[6-3H]6-Deoxy-5-ketoglucose was incorporated into neomycin, as efficiently as the well established precursor D-glucose, and wasfound to label exclusively the 2-deoxystreptamine ring of the antibiotic. The results strengthened the previous proposals that in the formation of 2-deoxystreptamine the C-6 hydroxyl group of D-glucose is removed prior to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…34 Initially, ratiometric labelling suggested the loss of the C-4 proton of D-glucose in the course of 2-DOS biosynthesis. 35,36 The in vitro conversion of D-glucose-6-phosphate into 2-DOS was observed in cell-free extracts of S. fradiae and was found to be NAD + -dependent, as expected for the proposed mechanism. 37, 38 Whereas the aforementioned in vivo labelling studies indicated loss of the C-4 hydrogen in the course of the cyclisation, in vitro conversion of [4-2 H]-D-glucose to 2-DOI was found to proceed with retention of the deuterium label; 39,40 the discrepancy may be explained by the kinetic isotope effect, which could cause untritiated substrate to be preferentially converted to product over the labelled compound, leading to depletion of the label in the product.…”
Section: Common Biosynthetic Intermediates 21 2-deoxystreptaminesupporting
confidence: 59%
“…34 Initially, ratiometric labelling suggested the loss of the C-4 proton of D-glucose in the course of 2-DOS biosynthesis. 35,36 The in vitro conversion of D-glucose-6-phosphate into 2-DOS was observed in cell-free extracts of S. fradiae and was found to be NAD + -dependent, as expected for the proposed mechanism. 37, 38 Whereas the aforementioned in vivo labelling studies indicated loss of the C-4 hydrogen in the course of the cyclisation, in vitro conversion of [4-2 H]-D-glucose to 2-DOI was found to proceed with retention of the deuterium label; 39,40 the discrepancy may be explained by the kinetic isotope effect, which could cause untritiated substrate to be preferentially converted to product over the labelled compound, leading to depletion of the label in the product.…”
Section: Common Biosynthetic Intermediates 21 2-deoxystreptaminesupporting
confidence: 59%
“…The majority of antibiotic BGCs carry genes with unknown or unassigned functions, and this work indicates that a salvage/recycling role could be a hypothesis to test for some of such genes. The existence of a “saving pathway” was reported for the biosynthesis of deoxysugars in neomycin 11 and landomycins, 12 putatively via a short sugar-activation pathway that was previously found for l -fucose. 52 The dTDP-glucose synthase-like protein LanZ2 was speculated to be involved in this short sugar-activation pathway but further genetic and biochemical evidence was required to fully address its function.…”
Section: Resultsmentioning
confidence: 73%
“… 10 However, there are rare examples of the salvage pathway in secondary metabolism. 11 13 In this study, we provided evidence of flavoenzyme CrmK-mediated substrate recycling in caerulomycin biosynthesis. Caerulomycins (CRMs) feature a 2,2′-bipyridine core structure and are produced by terrestrial Streptomyces caeruleus 14 and marine-derived Actinoalloteichus cyanogriseus WH1-2216-6.…”
Section: Introductionmentioning
confidence: 80%
“…2F-H e 2C-H e 3C-H a 3F-H a from experiments in which 6-deoxy-d-glucose derivatives were successfully incorporated into neomycin. 9 One can assume for organisms which produce deoxysugarcontaining natural products that the short activation is feasible for all deactivated 'intermediates' of a certain biosynthetic deoxygenation cascade. Thus, the results described here open up attractive options in the context of chemical and biochemical aspects of deoxysugars.…”
Section: Methodsmentioning
confidence: 99%